CT gastrography and enterography retrospective analysis: thickened diaphragm crura is a false indication for a gastric fundic tumor - Zhang, Xin; Wen, Ying; Wang, Qi; Chen, Manman; Yang, Ming; Han, Xiaoyu; Tang, Wenjuan; Shi, Heshui (Frontiers in Oncology, 2024)
ObjectivesTo mitigate the incidence of misdiagnosis and distinguish between gastric fundic tumors (GFTs) and thickened diaphragmatic crura (TDC).Materials and methodsComputed tomographic enterography (CTE) data from 3844 cases and computed tomographic gastrography (CTG) data from 4351 cases were retrospectively analyzed. A total of 105 cases were selected and categorized into three groups: 47 cases with TDC examined via CTE, 31 with adenocarcinoma, and 27 with gastrointestinal stromal tumors (GIST) examined via CTG. Inter-group differences in age, sex distribution, mass dimensions, mass-stomach interface (MSI), chief complaints, gastric underlying diseases, and enhancement patterns were analyzed.ResultsThe misdiagnosis rate of TDC as a tumor by radiologists is approximately 1.2% (47/3844). Age (p<0.05), sex ratio (p<0.05), mean mass size (p<0.05), chief complaint (p<0.05) and mass-stomach interface (MSI, p<0.05) were significantly different among patients with GIST, adenocarcinoma and TDC. The contrast enhancement pattern of TDC markedly differed from that observed in adenocarcinoma (p<0.05) and GIST (p<0.05) patients.ConclusionsMisdiagnosis of GFTs is occasionally and may be challenging to differentiate from TDC using CTE. To drastically lower the chance of misdiagnosis, this research aimed to assist radiologists in identifying and considering the possibility of TDC.